2011
DOI: 10.1371/journal.pone.0025038
|View full text |Cite
|
Sign up to set email alerts
|

Functional Studies on the IBD Susceptibility Gene IL23R Implicate Reduced Receptor Function in the Protective Genetic Variant R381Q

Abstract: Genome-wide association studies (GWAS) in several populations have demonstrated significant association of the IL23R gene with IBD (Crohn's disease (CD) and ulcerative colitis (UC)) and psoriasis, suggesting that perturbation of the IL-23 signaling pathway is relevant to the pathophysiology of these diseases. One particular variant, R381Q (rs11209026), confers strong protection against development of CD. We investigated the effects of this variant in primary T cells from healthy donors carrying IL23RR381 and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
87
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 46 publications
6
87
1
1
Order By: Relevance
“…suggested that IL-23R RQ381 exerted its protective effects by attenuation of IL-23-induced T H 17 functions (IL-17A production) without interfering with T H 17 differentiation (Pidasheva et al 2011). Further, Sarin et al (2011) showed that CD4 + CD45RO…”
Section: R381q Polymorphism: Mechanisms Of Actionmentioning
confidence: 98%
See 2 more Smart Citations
“…suggested that IL-23R RQ381 exerted its protective effects by attenuation of IL-23-induced T H 17 functions (IL-17A production) without interfering with T H 17 differentiation (Pidasheva et al 2011). Further, Sarin et al (2011) showed that CD4 + CD45RO…”
Section: R381q Polymorphism: Mechanisms Of Actionmentioning
confidence: 98%
“…On activation by IL-23, IL23R signals through a JAK/STAT pathway. IL23R associates constitutively with JAK2 (Pidasheva et al 2011). JAK proteins generally associate through their 4.1, ezrin, radixin, moesin (FERM) domains with membrane proximal regions of cytokine receptors.…”
Section: Il-23r Signaling Pathway In T H 17 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…JAK2 then phosphorylates STAT3 which then homodimerizes and translocates to the nucleus and triggers expression of cytokines, including IL-17A and IL-17F in T H 17 cells. Thus, IL-23 acts as a mediator of T H 17 cytokine production (Pidasheva et al, 2011;Safrany et al, 2013 (Guan et al, 2012). Some studies have indicated that R381Q variants confer protection from inflammatory diseases, including ankylosing spondylitis, psoriasis, and inflammatory bowel disease (Liu et al, 2010;Pidasheva et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, IL-23 acts as a mediator of T H 17 cytokine production (Pidasheva et al, 2011;Safrany et al, 2013 (Guan et al, 2012). Some studies have indicated that R381Q variants confer protection from inflammatory diseases, including ankylosing spondylitis, psoriasis, and inflammatory bowel disease (Liu et al, 2010;Pidasheva et al, 2011). With this regards, because RSA is related to inflammatory factors (IL-17 and IL-23) and T H 17 cells and the R381Q SNP can act as a regulator of inflammation, it occurred to us that there could be a relationship between expression of this SNP and the incidence of RSA in women.…”
Section: Introductionmentioning
confidence: 99%